(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This article is reflection on the actor puppeteer’s performance: the act of performing and the methods and processes an actor-puppeteer must develop when manipulating in full-view of an audience. Keywords: Performance. Puppet. Techniques. Artistic approaches.